2008
DOI: 10.1637/8174-111507-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Viruses Detected by Molecular Methods in Commercial Chicken and Turkey Flocks in the United States Between 2005 and 2006

Abstract: Intestinal samples collected from 43 commercial broiler and 33 commercial turkey flocks from all regions of the United States during 2005 and 2006 were examined for the presence of astrovirus, rotavirus, reovirus, and coronavirus by reverse transcription-polymerase chain reaction (PCR), and for the presence of groups 1 and 2 adenovirus by PCR. Phylogenetic analysis was performed to further characterize the viruses and to evaluate species association and geographic patterns. Astroviruses were identified in samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
125
1
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(150 citation statements)
references
References 43 publications
15
125
1
9
Order By: Relevance
“…In one study, Pantin-Jackwood et al (2007) found commercial turkeys to be negative for ARVs in the US. In a subsequent study, however, these authors (Pantin-Jackwood et al, 2008) reported ARVs in 62.80% of the chicken flocks and 45.50% of the turkey flocks tested. Previous studies have reported the presence of ARV in intestinal/faecal samples of broiler chickens (Koo et al, 2013;Mettifogo et al, 2014) although most of these studies indicated low prevalence of ARV as compared to other enteric viruses.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In one study, Pantin-Jackwood et al (2007) found commercial turkeys to be negative for ARVs in the US. In a subsequent study, however, these authors (Pantin-Jackwood et al, 2008) reported ARVs in 62.80% of the chicken flocks and 45.50% of the turkey flocks tested. Previous studies have reported the presence of ARV in intestinal/faecal samples of broiler chickens (Koo et al, 2013;Mettifogo et al, 2014) although most of these studies indicated low prevalence of ARV as compared to other enteric viruses.…”
Section: Discussionmentioning
confidence: 85%
“…Pantin-Jackwood et al (2008) also reported that three of the 43 broiler chicken flocks were negative for enteric viruses (astrovirus, reovirus, rotavirus and coronavirus). There are a number of factors (viruses, bacteria, protozoa, nutritional and management) other than the tested viruses that can cause enteritis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations